2018
DOI: 10.1111/bjd.16668
|View full text |Cite
|
Sign up to set email alerts
|

Children sustain high levels of skin DNA photodamage, with a modest increase of serum 25-hydroxyvitamin D3, after a summer holiday in Northern Europe

Abstract: Careful consideration must be given to the health outcomes of childhood solar exposure, and a much better understanding of the risk-benefit relationships of such exposure is required. Rigorous photoprotection is necessary for children, even in Northern Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Laboratory and modelling studies have shown that serum 25(OH)D can be increased with repeated suberythemal UVR exposure; such doses can be as low as four exposures of 0·375 SED over 24% BSA . A study of Polish children, who did apply sunscreen, on holiday by the Baltic Sea showed that daily borderline erythemal exposure results in a highly significant increase of serum 25(OH)D 3 . These studies suggest that vitamin D synthesis occurs with low UVR doses and therefore sufficient UVR may be transmitted through a sunscreen for vitamin D synthesis.…”
Section: Conclusion and Recommendations From Panel Discussionmentioning
confidence: 99%
“…Laboratory and modelling studies have shown that serum 25(OH)D can be increased with repeated suberythemal UVR exposure; such doses can be as low as four exposures of 0·375 SED over 24% BSA . A study of Polish children, who did apply sunscreen, on holiday by the Baltic Sea showed that daily borderline erythemal exposure results in a highly significant increase of serum 25(OH)D 3 . These studies suggest that vitamin D synthesis occurs with low UVR doses and therefore sufficient UVR may be transmitted through a sunscreen for vitamin D synthesis.…”
Section: Conclusion and Recommendations From Panel Discussionmentioning
confidence: 99%
“…These findings were attributed to the fact that high UVA sunscreen allows transmission of more UVB than low UVA sunscreen. Another very important study on sun exposure and vitamin D levels followed Polish children over 12 days at a Baltic Sea summer camp [31]. Relatively low daily UV radiation doses resulted in a modest but significant improvement in 25(OH)D (24%) but a very much greater increase in CPD (1162%).…”
Section: Vitamin D Intake Recommendations Evaluation Of Sufficiencymentioning
confidence: 99%
“…However many skin experts suggest that all sun exposure is detrimental, even very short exposures, due to the cumulative effects of radiation exposure to the skin. One recent study suggested increased skin damage in children after exposing skin to the sun on holiday in Northern Europe [81], but this study has been criticised as the children were exposed to 6-7 hours of sun a day, which is far greater than that needed for adequate vitamin D synthesis, and use of sunscreen after an initial short period of unprotected skin exposure around noon would have reduced the skin damage but still have the benefit of producing vitamin D (commentary by Webb [82]. The subjects were also relatively vitamin D sufficient so would not be expected to make large gains in vitamin D status [82].…”
Section: Recommendations For Safe Sunlight Exposurementioning
confidence: 99%